2005
DOI: 10.1111/j.1447-0756.2005.00248.x
|View full text |Cite
|
Sign up to set email alerts
|

Reference birth‐length range for multiple‐birth neonates in Japan

Abstract: The birth length of twins was smaller than that of singletons, but the difference was smaller than the difference in birthweight between twins and singletons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…Since discordant twins might be Appropriate for Gestational Age (AGA)/Small for Gestational Age (SGA), AGA/AGA or AGA/Large for Gestational Age (LGA), the intrauterine growth status of every twin in discordant group was defined as AGA, LGA or SGA according to Kato's growth charts. 8 For every twin pair, obstetric complications such as pre-eclampsia, diabetes mellitus, chronic hypertension, premature rupture of membranes (>18 h before birth) were recorded. Maternal age younger than 18 and older than 35 and use of artificial fertilization techniques (ovulation induction, intrauterine sperm injection etc.)…”
Section: Methodsmentioning
confidence: 99%
“…Since discordant twins might be Appropriate for Gestational Age (AGA)/Small for Gestational Age (SGA), AGA/AGA or AGA/Large for Gestational Age (LGA), the intrauterine growth status of every twin in discordant group was defined as AGA, LGA or SGA according to Kato's growth charts. 8 For every twin pair, obstetric complications such as pre-eclampsia, diabetes mellitus, chronic hypertension, premature rupture of membranes (>18 h before birth) were recorded. Maternal age younger than 18 and older than 35 and use of artificial fertilization techniques (ovulation induction, intrauterine sperm injection etc.)…”
Section: Methodsmentioning
confidence: 99%
“…According to many reports (Bleker et al, 1979;Kato, 2004), the average birth weight of boys is usually slightly higher than the birth weight of girls in a healthy population. Studies of the Carpathian newborns (low polluted control material) for over 18 years, showed no statistically significant differences between the birth weight of boys and girls (3490 ± 58.2; n = 108 vs 3443 ± 64.4; n = 119 respectively).…”
Section: The Clinical Characteristics Of the Studied Groupsmentioning
confidence: 99%
“…In the study by Kato et al 18 the mean birth weight of twin pregnancies was also lower: 2,590 gm for the first twin and 2,560 for second twin. The difference between weight of newborns may reflect the difference in quality of perinatal care and consequently the mean age on delivery and fetal growth retardation.…”
Section: Resultsmentioning
confidence: 83%